2011
DOI: 10.1523/jneurosci.2388-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 5 Regulates PSD-95 Ubiquitination in Neurons

Abstract: The kinase Cdk5 and its activator p35 have been implicated in drug addiction, neurodegenerative diseases such as Alzheimer’s, learning and memory, and synapse maturation and plasticity. However the molecular mechanisms by which Cdk5 regulates synaptic plasticity are still unclear. PSD-95 is a major postsynaptic scaffolding protein of glutamatergic synapses that regulates synaptic strength and plasticity. PSD-95 is ubiquitinated by the Ubiquitin E3 Ligase Mdm2, and rapid and transient PSD-95 ubiquitination has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…In contrast to Colledge et al (25), we found that, at least in our experimental system, NMDA-induced PSD-95 degradation was not proteasome-dependent because it could not be prevented by a variety of proteasome inhibitors. This is in line with the findings of Bianchetta et al (26), who did not find proteasomal degradation of PSD-95 and suggested a non-proteolytical regulatory function for ubiquitinated PSD-95 in the regulation of NMDAinduced AMPA receptor endocytosis. Still, NMDA-induced degradation of PSD-95 was impaired in the absence of LRP1 (Fig.…”
Section: Nmda-dependent Degradation Of Psd-95 Is Delayed and Reduced supporting
confidence: 93%
“…In contrast to Colledge et al (25), we found that, at least in our experimental system, NMDA-induced PSD-95 degradation was not proteasome-dependent because it could not be prevented by a variety of proteasome inhibitors. This is in line with the findings of Bianchetta et al (26), who did not find proteasomal degradation of PSD-95 and suggested a non-proteolytical regulatory function for ubiquitinated PSD-95 in the regulation of NMDAinduced AMPA receptor endocytosis. Still, NMDA-induced degradation of PSD-95 was impaired in the absence of LRP1 (Fig.…”
Section: Nmda-dependent Degradation Of Psd-95 Is Delayed and Reduced supporting
confidence: 93%
“…Proteins were eluted with 0.1 M glycine-HCl buffer, pH 2.1, and then enzymatically digested with Glu-C to ensure that cysteine-containing peptides were of proper length (ϳ500 -3000 Da) for optimum MS/MS by high energy collisional dissociation fragmentation in a Hybrid Orbitrap Elite MS system. Similar LC MS/MS were carried out as described previously (39). Collected MS and MS/MS data were peak-picked with MASCOT Distiller and searched against the Swiss Prot Human protein database utilizing an in-house MASCOT algorithm (version 2.2.0).…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary findings have already shown that Cdk5 is also pivotal to postsynaptic compartment, where exists a lot of substrates of Cdk5, such as NMDAR [90], PSD-95 [91], DARPP-32 [42], and dopamine D2 receptor [33]. Cdk5 can modulate the function of NMDAR, which is related to the induction of some forms of synaptic plasticity; for example, the NMDAR-dependent Hebbian long-term potentiation (LTP) and long-term depression (LTD).…”
Section: Cdk5 Modulates Synaptic Plasticitymentioning
confidence: 99%
“…Also, an inhibition of Cdk5 displays an enhancement of learning and plasticity owning to an increased NR2B levels at the synapse triggered by disturbing calpain/ NR2B complex [90]. Moreover, Cdk5 mediates the regulation of the scaffold protein PSD-95 expression, which can fasten NMDA receptors to the postsynaptic density [91]. The scaffold protein PSD-95, prime ingredient of postsynaptic density, is known to transfer signal to neurotransmitter receptors.…”
Section: Cdk5 Modulates Synaptic Plasticitymentioning
confidence: 99%